Antihyperglycemic Activity of Houttuynia cordata Thunb. in Streptozotocin-Induced Diabetic Rats - Manish Kumar; Satyendra K. Prasad; Sairam Krishnamurthy; Siva Hemalatha (Advances in Pharmacological Sciences)
Present study is an attempt to investigate plausible mechanism involved behind antidiabetic activity of standardized Houttuynia cordata Thunb. extract in streptozotocin-induced diabetic rats. The plant is used as a medicinal salad for lowering blood sugar level in North-Eastern parts of India. Oral administration of extract at 200 and 400 mg/kg dose level daily for 21 days showed a significant (P<0.05) decrease in fasting plasma glucose and also elevated insulin level in streptozotocin-induced diabetic rats. It also significantly reversed all the alterations in biochemical parameters, that is, total lipid profile, blood urea, creatinine, protein, and antioxidant enzymes in liver, pancreas, and adipose tissue of diabetic rats. Furthermore, we have demonstrated that the extract significantly reversed the expression patterns of various glucose homeostatic enzyme genes like GLUT-2, GLUT-4, and caspase-3 levels but did not show any significant effect on PPAR-γ protein expressions. Additionally, the extract positively regulated mitochondrial membrane potential and succinate dehydrogenase (SDH) activity in diabetic rats. The findings justified the antidiabetic effect of H. cordata which is attributed to an upregulation of GLUT-4 and potential antioxidant activity, which may play beneficial role in resolving complication associated with diabetes.